Effect of Neurofeedback 2D and 3D Stimulus Content on Stress Mitigation - Hafeez, Y. (Institute of Electrical and Electronics Engineers Inc., 2019)
The EEG-neurofeedback modality has direct implication on alpha asymmetry. The efficacy of EEG-neurofeedback may be affected by the stimulus contents. This research investigated the effectiveness of 2D and 3D game stimulus content (GSC) on stress mitigation during neurofeedback training (NFT). The effectiveness is compared between stimulus contents by measuring the mean prefrontal alpha asymmetry using quantitative Electroencephalogram (qEEG) analysis. For this, ten healthy participants among university students were recruited and performed twenty-minutes neurofeedback training (NFT) on Fp1-Fp2 within a period of sixty days to record forty sessions of data. The statistical analysis of the data after the neurofeedback training showed an effect of game contents on alpha asymmetry. The graphical analysis of alpha power showed that the 3D game content was more effective than the 2D game content. The outcome of 3D game stimulus content showed effect on the prefrontal alpha asymmetry and improve the treatment efficacy of neurofeedback for stress mitigation. Â© 2019 IEEE.